2020
DOI: 10.3390/atmos11040433
|View full text |Cite
|
Sign up to set email alerts
|

NOx Emission Reduction and Recovery during COVID-19 in East China

Abstract: Since its first confirmed case at the end of 2019, COVID-19 has become a global pandemic in three months with more than 1.4 million confirmed cases worldwide, as of early April 2020. Quantifying the changes of pollutant emissions due to COVID-19 and associated governmental control measures is crucial to understand its impacts on economy, air pollution, and society. We used the WRF-GC model and the tropospheric NO2 column observations retrieved by the TROPOMI instrument to derive the top-down NOx emission chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
166
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(180 citation statements)
references
References 30 publications
13
166
0
1
Order By: Relevance
“…Their results reveal that levels of polluting gases fell by about 45% after two weeks. Similar findings are reported in Thailand ( Stratoulias and Nuthammachot, 2020 ), China and Japan ( Ma and Kang, 2020 ; Zhang et al, 2020 ), Ecuador ( Zalakeviciute et al, 2020 ), Iran ( Broomandi et al, 2020 ), Milan, Italy ( Collivignarelli et al, 2020 ) and Morocco ( Otmani et al, 2020 ). Siciliano et al (2020) and Zhao et al (2020) , in turn, identified noteworthy increases in ozone concentrations (O 3 ) during the measures of social distancing adopted respectively by Brazil and China.…”
Section: Resultssupporting
confidence: 81%
“…Their results reveal that levels of polluting gases fell by about 45% after two weeks. Similar findings are reported in Thailand ( Stratoulias and Nuthammachot, 2020 ), China and Japan ( Ma and Kang, 2020 ; Zhang et al, 2020 ), Ecuador ( Zalakeviciute et al, 2020 ), Iran ( Broomandi et al, 2020 ), Milan, Italy ( Collivignarelli et al, 2020 ) and Morocco ( Otmani et al, 2020 ). Siciliano et al (2020) and Zhao et al (2020) , in turn, identified noteworthy increases in ozone concentrations (O 3 ) during the measures of social distancing adopted respectively by Brazil and China.…”
Section: Resultssupporting
confidence: 81%
“…However, emissions from residential heating and industry remained steady or slightly declined (Chen et al 2020). Using satellite data, Zhang et al (2020) and the National Center for Atmospheric Research (Worden et al 2020) reported a 70% and 50% decrease in NO x concentrations in Eastern China, respectively. Bao and Zhang (2020) showed an average of 7.8% decrease in the Air Quality Index over 44 cities in northern China.…”
Section: Introductionmentioning
confidence: 99%
“…While COVID-19 restrictions have reduced carbon emissions, alongside other GHGs, pollutants, and aerosols, the easing of these restrictions is likely to see an uptick in emission levels. This has already been noted in parts of China, the earliest affected region of the pandemic [11,12]. One suggested approach emerging from the pandemic is the concept of 'glocalization'.…”
Section: Achievement Of Carbon Targets and The Energy Transitionmentioning
confidence: 86%
“…Focusing on nitrogen oxides (NO x ), it was confirmed that levels decreased considerably (~50%) for most provinces compared to pre-COVID-19 lockdowns, and only moderately rebounded (~26%) after back-to-work orders were issued for most eastern Chinese provinces. Wuhan was an exception, where NO x levels remained low, even into March 2020 [12]. Considering the impact of reduced mobility, an almost 70% reduction in human mobility in 44 cities in northern China lead to significant decreases in SO 2 (6.76%), PM 2.5 , and PM 10 (5.93% and 13.66%), NO 2 (24.67%) and CO (4.58%), highlighting the flow-on impacts of decreased mobility on industrial and commercial activities linked to our daily lives [13].…”
Section: Reduced Mobility Aerosols and Ghg Emissionsmentioning
confidence: 99%